Effects of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Davis, Shania; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Since newborn piglets don’t have the iron stores like other baby animals, it is imperative to administer iron at a young age. Iron Dextran is the most commonly used iron supplement but Gleptaforte, another injectable iron, is now an alternative. However, there is the problem of how much Gleptoforte is appropriate for an injection in a 3-day old piglet at processing to provide enough iron to prevent anemia. This study is used to evaluate the performance and blood parameters of newborn pigs given different quantities of Gleptoforte. A total of 336 pigs (DNA 241x600) were used in this 21-day farrowing study. The 28 litters used were equalized at farrowing to each sow. At processing, all piglets were weighed and six barrows and six gilts per litter were given 1 of 6 treatments. Treatments included the negative control of 0mg, 50mg, 100mg, 150mg, 200mg, and 200mg + 100mg booster at day 11 of Gleptoforte. The 56 piglets in each treatment was placed by randomized design. Blood collection of one barrow from each treatment and each litter and weight collections of all piglets were taken on day 3, day 11, and day 21 to determine average daily gain (ADG), body weight, hemoglobin (Hgb), hematocrit (Hct), serum iron, and total iron binding capacity (TICB). This study tells us that the day 21 body weight and ADG both increased as the dosage of Gleptaforte increased. However, nothing showed that the additional booster at day 11 improved ADG or Body Weight. All blood parameters show that the 0mg dose gave the lowest values and 200mg dose gave the highest values, respectively. On day 21, the blood collections for Hgb, Hct, and Serum Iron, all showed a significant difference (p<0.05) between the 200mg dose and the 200mg + 100mg dose with the 200mg + 100mg dose being the greater. However, TCIB, body weight, and ADG did not show any difference between the 200mg dose and the 200mg + 100mg dose. In conclusion, the dose of 100mg of Gleptoforte gave us the best results in growth performance and the dose of 200mg + 100mg provided an increase in hematological parameters but was not effective in performance before weaning.
Keywords: Fall 2017